Self-Gravitational Shock Potential in Degenerate Quantum Plasmas - Asaduzzaman, Muhammad (Journal of Engineering Science, 2025)
A rigorous theoretical investigation has been made on the propagation of nonlinear self-gravito-acoustic shock structures (SGASSs) in a quantum plasma system consisting of non-inertial degenerate non-relativistic electron species and inertial non-degenerate heavy nucleus species. The nonlinear behaviors for this self-gravitational perturbation (SGP) mode in planar geometry has been examined. The Burgers equation has been derived by employing the standard reductive perturbation technique. To analyze the Burgers equation numerically, the solution of the Burgers equation has been obtained for stationary localized condition. The dissipative force, which is effective on heavy elements, plays vital role for the formation of SGASSs in the plasma system under consideration. The non-relativistic limit has great effect on the basic properties (amplitude, width, etc.) of the SGASSs. The obtained results are applicable in white dwarfs and neutron stars which are the most common examples of astrophysical compact objects. Journal of Engineering Science 16(1), 2025, 31-36